Effects on the wellness state in the period of confinement due to COVID-19 in professional soccer players - Merino-Muñoz, Pablo; Pérez-Contreras, Jorge; Adasme-Maureira, Felipe; Aedo-Muñoz, Esteban (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2021)
This study aimed to find changes in the wellness state, during the confinement period due to COVID-19, in professional soccer players from the first division B of Chile. The studied sample consisted of 28 professional male soccer players aged 26 ± 6.3 years, body mass 74.2 ± 5.5 kg, and height 177 ± 0.05 cm. The degree of well-being was evaluated through a questionnaire (McLean et al., 2010) during the 2020 competitive and confinement periods. Statistically, significant differences (p